Implementasi Aplikasi Ritel DC Leu Mart Karawang dengan Metode Electronic Data Interchange (EDI) - Candra Galang Gemilang Putra; Lailia Azizatul Magfiroh (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Distribution to meet daily needs from distribution centers to large agents, shops, and large stalls to small stalls is required to be carried out quickly and responsively in the distribution process. As a distributor, you are also required to always be able to manage the amount of stock in the warehouse, so that there is no accumulation of stock or a shortage of product stock provided. To avoid miscommunication between the sales of the LEU Mart Karawang Distribution Center and the DC Leu Mart Karawang warehouse. In connection with the problems that occur in the distribution center, it is necessary to apply communication technology to speed up communication in the distribution center. The application or implementation of the LEU Mart Karawang Distribution Center retail transaction application using the Electronic Data Interchange (EDI) method which is applied in this study. The application applied to DC LEU Mart Karawang can improve the distribution process and warehouse inventory control of DC LEU Mart Karawang. Apart from that, applying the EDI method can also provide information quickly directly without having to control directly to the distribution warehouse. Based on this study, it was found that the importance of the application of information technology to facilitate the ongoing distribution process.